2021
DOI: 10.1007/s42844-021-00035-9
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status Moderates the Impact of Emotional but not Physical Childhood Abuse on Women’s Sleep

Abstract: A recent systematic review highlighted associations between childhood abuse and adult sleep quality, and the need for research focused specifically on women and the role of moderating variables. The objectives of the present study were (1) to assess the impact of frequent physical and emotional child abuse on adult sleep among women; and (2) to assess the role that childhood socioeconomic status (SES) could play in moderating these associations. In-person data were collected from women living in a mid-sized ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…The participants who experienced emotional and physical abuse were categorized in the high-decreasing sleep score group. Our results are consistent with previous studies [30][31][32]. However, unlike previous studies, we took into consideration longitudinal changes in sleep quality.…”
Section: Discussionsupporting
confidence: 92%
“…The participants who experienced emotional and physical abuse were categorized in the high-decreasing sleep score group. Our results are consistent with previous studies [30][31][32]. However, unlike previous studies, we took into consideration longitudinal changes in sleep quality.…”
Section: Discussionsupporting
confidence: 92%
“…It is also worthwhile for future research to explore potential effect modifiers such as socioeconomic status and gender in the associations between adverse/positive childhood experiences and inflammation. Prior research indicated both socioeconomic position and gender as modifiers of the relationship between adverse experiences and health outcomes ( Currie et al, 2021 ; Lacey et al, 2020 ). Further investigation will be helpful to understand the mechanisms linking these early life experiences and physiological dysfunction and to inform upstream intervention opportunities in practice.…”
Section: Discussionmentioning
confidence: 99%